2022
DOI: 10.1038/s43705-022-00131-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and high-fat diet differentially alter the gut microbiota composition and metabolic function in lean versus obese mice

Abstract: There are known associations between opioids, obesity, and the gut microbiome, but the molecular connection/mediation of these relationships is not understood. To better clarify the interplay of physiological, genetic, and microbial factors, this study investigated the microbiome and host inflammatory responses to chronic opioid administration in genetically obese, diet-induced obese, and lean mice. Samples of feces, urine, colon tissue, and plasma were analyzed using targeted LC-MS/MS quantification of metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 105 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…To control for the succession effects of a serial dietary intervention, we fed the mice the 20% soy diet or the 20% casein diet as a control at the end of the diet series. We analyzed samples from all mice and diets using an integrated metagenomic-metaproteomic approach 12,18 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To control for the succession effects of a serial dietary intervention, we fed the mice the 20% soy diet or the 20% casein diet as a control at the end of the diet series. We analyzed samples from all mice and diets using an integrated metagenomic-metaproteomic approach 12,18 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The microbiota’s response to the yeast protein diet warrants further investigation in the context of potential implications for host health especially in light of literature suggesting yeast as a potential probiotic 44 . Previous studies in mice have shown that diets which promote bacteria and their enzymes that degrade the mucins in the intestinal mucus layer 6,12 can make the host more susceptible to enteric inflammation and infection 6,35 . The fact that B. theta shows a similar gene expression response to egg white protein and mucin in vivo and in vitro suggests that egg white protein promotes bacteria and enzymes that also degrade mucin, which could have negative implications for the host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's worth noting that sialidase (K01186, sialidase-1 [EC: 3.2.1.18]) hydrolyzes MUC2, a highly O-glycosylated polysaccharide in the intestinal whose terminal position is occupied by monosaccharide sialic acid and can be cleaved by sialidase [42]. The differential analysis of the gene encoding the starch-bound outer membrane protein SusE/F (K21572) revealed signi cant increases in lysosomal acid hydrolytic glycoside genes, namely K01186, K01206, and K12373 which can release the different components of mucin glycans [43]. This increase was accompanied by upregulation of genes such as K00688 (glycogen phosphorylase [EC: 2.4.1.1]), K00975 (glucose-1phosphate adenylyltransferase [EC: 2.7.7.27]), and K01223 (6-phospho-beta-glucosidase [EC: 3.2.1.86]), suggesting variations in glucose metabolism.…”
Section: The Classi Cation and Variation Patterns Of Bshs In Gut Micr...mentioning
confidence: 99%
“…Antibiotics are well known to significantly impact the intestinal microbiome, with effects possibly lasting for months to years after antibiotic exposure and even impacting the efficacy and safety of other drugs and vaccines [49,[141][142][143][144]. Many drugs with non-microbial targets, and even pharmaceutical excipients, have also been identified as affecting microbiota [145][146][147][148][149][150]. Such effects should be appreciated when delivering medicines to the colon; drugs with negative microbiome effects may be less suitable for colonic delivery, and those with positive microbiome effects could represent opportunities for new targeted treatments [151,152].…”
Section: The Microbiomementioning
confidence: 99%